Evaluation of Bone Mineral Density in Subjects with Primary Hyperparathyroidism by Dual Energy X-Ray Absorptiometry (Bangladesh Journal of Nuclear Medicine, 2018)
Objective: Bone loss is a major complication of primary hyperparathyroidism (PHPT), and the extent of bone loss is an important factor for parathyroidectomy. Studies focused on this issue of bone loss in subjects with PHPT are quite rare in our country. This study will help the physicians to take proper action by giving an exact reflection of bone condition in subjects with PHPT. The purpose of this study was to evaluate the bone condition by measuring Bone Mineral Density (BMD), in subjects with PHPT using Dual Energy X-ray Absorptiometry (DEXA) and compare these findings with individuals without PHPT.Patients and Methods: It was an analytic cross sectional study (group comparison) carried out at National Institute of Nuclear Medicine and Allied Sciences (NINMAS) BSMMU campus, Dhaka from July 2015-December 2016. Subjects of PHPT diagnosed by biochemical evaluation (increased serum calcium and parathyroid hormone concentrations), between age ranges 15-45 years were selected as group-A. Individuals without biochemical evidence of PHPT or other major illness causing bone loss were selected as comparison group or as group-B. The subjects underwent BMD test by DEXA at lumbar spines from L1-L4 vertebra and the left femoral neck using Norland XR-46 densitometer. BMD was classified according to WHO criteria. Data presented on categorical form were analyzed using chi-squared test. While the data presented on continuous scale were analyzed using student’s t-test. In each analysis, level of significance was 5% and P value